IMPLEMENTASI PEMBELAJARAN BERBASIS LITERASI SAINS PISA 2025 BERBANTUAN VIRTUAL LAB PHET BAGI MAHASISWA CALON GURU SD - Siti Zahra Mulianti Natsir (STKIP Subang, 2026)
This study aimed to describe the implementation of science literacy-based learning assisted by the PhET Virtual Lab on the topic of dynamic electricity, designed in accordance with the PISA 2025 framework. The study employed a descriptive quantitative method involving 96 PGSD students from three classes at a Teacher Education Institution (LPTK) in Makassar City. The learning activities included case analysis, virtual experiments, the development of educational posters, and community outreach activities. Data were collected using a learning implementation observation sheet and analyzed descriptively using percentages. The results indicated that all stages of the learning process were implemented very well and successfully facilitated the integration of scientific competencies, scientific knowledge, environmental science, and science identity within a unified learning experience. These findings suggest that science literacy-based learning assisted by the PhET Virtual Lab has the potential to serve as a relevant instructional strategy for supporting the implementation of the PISA 2025 framework in the education of prospective elementary school teachers.